The Rough guide to egypt - Richardson, Dan; Jacobs, Daniel; Meghji, Shafik (United States Rough guides, 2010)
The Rough Guide to Egypt" is your essential travel guide to this ancient land. Fully revised and updated, the guide provides unparalleled coverage of everything from Egypt's tombs, temples and pyramids to diving in the Red Sea, desert safaris and cruising the Nile in style. With accurate maps, plans, colour spreads and beautiful colour photography throughout; you'll find informed practical advice on what to see and do in Egypt, plus honest reviews of the best hotels, clubs, shops and restaurants for all budgets. Adventurous, informative and opinionated
"Make the most of your time on earth"
Includes indexes
Indexed maps of Egypt and transport maps
Keywords: Automobile travel -- Guidebooks; Costume; Transportation; Egypt -- Maps, Tourist